Factibilidad para la Creación de una Empresa de Producción y Comercialización de Geranio Egipcio y Naranja (Hierbas Aromáticas), con Stevia (Endulzante Natural) en Sobre de Papel Filtro, en la Ciudad de Loja - Ramírez Jiménez, Jhuliana Patricia (2016)
The present investigation was carried out with the purpose of carrying out a "FEASIBILITY FOR THE CREATION OF A COMPANY OF PRODUCTION AND MARKETING OF EGYPTIAN AND ORANGE GERANIUM (AROMATIC HERBS), WITH STEVIA (NATURAL ENDULZANT) IN FILTER PAPER ENVELOPE, IN THE CITY OF SHOP ". For this reason, the objective of this project is to provide consumers with a product with added value such as Egyptian and orange geranium with stevia in filter paper envelope, taking advantage of existing resources, skilled labor, raw material and contributing to the Improve the economic situation of our province and in turn improve the productivity of it. In order to obtain literature review information and to base the project, research methods and techniques were used, the research work was descriptive in character, describing the capacity of the problem; Then the technique of the survey applied to the families of the city of Loja was taken into account with a sample of 381 surveys and another one to the offerers of infusion envelopes in the city. We then analyzed all the aspects found in the present study. The market study analyzed the demand and supply to determine the reception of the product in the market, within the technical study analyzed the capabilities of the company in which is installed and used; As well as the size and location, layout of the plant, project engineering and organic - functional structure. The financial study determined the investment of the project, which is $ 48,739.07 dollars, which will be financed with a contribution from the partners of 58.97% of the total investment corresponding to $ 28,739.07 and a loan that Will remain with the Development Bank will constitute 41.03% which corresponds to 20,000.00 dollars to 5 years term. The results of the present study determined the feasibility of the project, according to financial indicators such as: Net Present Value (NPV) of $ 18,380.28, Internal Rate of Return (TIR) 20.20%, Capital Recovery Period (PRC) is 3 years, 0 months and 10 days, Cost Benefit Ratio (RBC) is 1.25, and Sensitivity Analysis indicates that the project supports an increase in costs of 6.43%, and a decrease Of revenues of 5.09%. It can be concluded that according to the analyzes of the present study the project is feasible.